Rapid Onset of Hippocampal Atrophy in Febrile-Infection Related Epilepsy Syndrome (FIRES). (April 2014) - Byler, Debra L.; Grageda, Melissa R.; Halstead, E. Scott; Kanekar, Sangam
Febrile infection-related epilepsy syndrome (FIRES) is a catastrophic and usually refractory epilepsy syndrome that occurs after a febrile illness in previously normal children. The pathogenesis of the syndrome is unknown, and the diagnosis is typically made by exclusion after an exhaustive negative workup for central nervous system infections and autoimmune or metabolic disorders. Magnetic resonance imaging of patients with this condition has previously shown hippocampal abnormalities, typically found several months or longer after initial seizures. We report a previously healthy 5-year-old child who developed hippocampal atrophy by day 37 of his illness. The development of early hippocampal atrophy in this epileptic encephalopathy may provide insight into pathogenesis and highlights the need for aggressive and effective interventions early in the disease process.